What is older adults’ understanding of Alzheimer's disease research registries? Findings from 20 focus group studies - Litty Samuel; Katelynn Kuijpers; Erin K. Maloney; Jessica B. Langbaum; Amy Bleakley (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
ABSTRACT INTRODUCTION Research registries address the challenges associated with enrollment of individuals in research studies by matching members to current studies and trials in need of participants. However, recruitment into research registries can be challenging as many lack awareness regarding research registries and need to be educated on their existence, purpose, and significance. METHODS The present study uses data from 20 online focus groups conducted in English with Black (n = 89), White (n = 83), and Hispanic (n = 44) older adults to investigate their understanding of research registries. Participants were recruited through paid advertisements, and the focus groups were conducted between September 2022 and 2023 with a sample of 188 adults. RESULTS There was a general lack of awareness about Alzheimer's disease (AD) research registries. Participants expressed unfamiliarity with the concept of AD research registries, confusion about eligibility criteria and their purpose, and often conflated them with individual clinical trials. DISCUSSION Research registries can play a crucial role in identifying and referring potential participants to AD prevention studies. Given the lack of understanding about registries, interventions such as messaging with familiar language can help to address lack of awareness and increase enrollment into AD research registries. Highlights A better understanding of older adults’ perceptions about research registries. More relatable and easy‐to‐comprehend messaging is needed to raise awareness of research registries. Targeted messaging strategies are needed to recruit participants directly into Alzheimer's disease (AD) clinical trials.